Development and validation of a Sarcopenia Geriatric Scale (SARCO-GS): a new short scale for the screening of sarcopenia - Rosas-Carrasco, Oscar; Omaña-Guzmán, Isabel; García-González, Ana Isabel; Luna-López, Armando (Frontiers in Endocrinology, 2023)
Introduction. Sarcopenia is a highly prevalent disease associated with adverse outcomes such as falls, disability, and death. The current international consensuses agree that muscle strength, muscle mass, and gait speed must be included in the definition. However, these proposed criteria require objective 2 This is a provisional file, not the final typeset article measurements that are not available for most populations. Since the timely identification of sarcopenia is a priority, several subjective screening scales have been developed; however, they have some limitations due to their low sensitivity. The objective of this work was to develop and validate SARCO-GS, a new short scale to screen sarcopenia that complies with being affordable, easy, and accessible for all clinical care settings.Materials. The development of the SARCO-GS included four stages: (1) Review and analysis of documentary sources; (2) Contextualization of the theoretical model of sarcopenia; (3) Scale conformation; (4) Reliability and validity analyses. SARCO-GS was validated in the FraDySMex study, which is a longitudinal cohort of community-dwelling adults.Results. In the studied population (n=852), the average age was 68.9 years (SD 10.21) and 80.1% of the participants were female. SARCO-GS is a 7-item scale with an innovative structure that included five subjective questions (gait speed, muscular strength, muscle mass) and two measurements of muscular strength and muscle mass (Chair stand test and calf circumference). The results regarding criterion validity showed that the cut-off point ≥ 3 had good sensitivity (77.68%) versus the EWGSOP2 consensus, with an adequate Area Under the Receiver Operating Characteristic (AUC) (0.73), in addition to showing higher values of sensitivity and AUC than SARC-F and SARC-CalF using as reference the same consensus. Furthermore, SARCO-GS presented good predictive validity for functional dependence (HR=2.22, p=0.046) and acceptable correlation with other related measurements (construct validity). Regarding reliability, the scale showed acceptable internal reliability (correlation between items and total score: 0.50 to 0.70). After the validation analysis, the scale was adapted to English.The SARCO-GS is a novel scale to screen sarcopenia with high sensitivity, good construct, predictive validity, and internal reliability that may be useful for health professionals in different clinical settings and for clinical research.